An investigation of antecedents and consequences of consumers' attitudes towards an apparel website. (2015) - Lee, Zui Chih; Hodges, Nancy; Watchravesringkan, Kittichai
There is a fast-growing percentage of consumers shopping online in the US, and retailers has profited from this new channel. Little is known about how a website provides competitive advantage to a retailer and what makes a website appealing to consumers. The purpose of this research is to examine the relationship between website attributes (e.g. perceived attractiveness, informativeness), e-service quality (e.g. efficiency, fulfilment, system availability) and consumer-company identification for online information search and purchase behaviour. Specifically, this research examines the links between consumer-company (C-C) identification, perceived usefulness and attitude towards a website, as well as information search and purchase intention. A conceptual model is developed combining elements from social identity and the technology acceptance model, from which seven hypotheses are developed. Structural equation modelling was applied to test the relationships based on a convenience survey sample of 291 university students. Findings revealed that six of the seven hypothesised relationships were supported.